Comparing Institution-Building in East Asia - Yoshimatsu, H. author. aut Link
XI, 231 p.
Keywords: Yoshimatsu explores the causes and implications of the diverse degree of institution-building in East Asia by examining two processes of initiating and developing multilateral institutions in five policy areas: trade, finance, food security, energy security, and the environment.